The Relationship Between Teacher Job Satisfaction, Teacher Saturation and Principal Leadership Style in Private Schools in Bandung City - Fazrian Thursina; Yana Priyana (West Science Social and Humanities Studies, 2023)
This study aims to investigate the relationship between teacher job satisfaction, teacher burnout, and principal leadership style in private schools in Bandung City. A total of 90 teachers from five private schools participated in this study. Data was collected through a self-reported survey that included measures of teacher job satisfaction, teacher burnout, and principal leadership style. The results of the study show that teacher job satisfaction is positively related to the principal's leadership style and negatively related to teacher job burnout. In addition, the study results show that principals in private schools in the city of Bandung are seen as using a transformational leadership style, which is positively related to teacher job satisfaction. These findings suggest that supportive leadership and well-managed workload are important in enhancing teacher job satisfaction and effective leadership in private schools. These findings have important implications for school administrators and policy makers in increasing teacher job satisfaction and improving the quality of education in private schools in Bandung City and outside Bandung City.